A severe case of acute exogenous lipoid pneumonia treated with systemic corticosteroid. (2016) - Yasui, Hideki; Yokomura, Koshi; Suda, Takafumi
Abstract: Acute exogenous lipoid pneumonia is a rare disorder in adults. A treatment of choice for lipoid pneumonia has not been established, and systemic corticosteroid use remains controversial. We report the case of a 32-year-old man with schizophrenia who presented with kerosene-induced acute exogenous lipoid pneumonia that was treated with a systemic corticosteroid. In this case, supportive therapy did not improve the patient's condition, so systemic corticosteroid therapy was commenced four days after he ingested the kerosene. After corticosteroid commencement, the patient's symptoms and hypoxia improved within a few days. Although some radiological characteristics of this disorder have been reported previously, the process of radiological improvement of exogenous lipoid pneumonia is not well known. In this case, computed tomography findings changed dramatically after corticosteroid therapy was initiated. Extensive bilateral consolidations that were observed on admission improved. Although pneumatoceles developed two weeks after corticosteroid commencement, they were nearly gone after two months of the treatment. While corticosteroid therapy is not suitable for all cases, it should be considered for severe or refractory cases.